Aspectos da biologia e ecologia de Callibaetis guttatus Navás, 1915 (Insecta: Ephemeroptera: Baetidae) em alagados temporários da Restinga de Maricá, Estado do Rio de Janeiro, com considerações taxonômicas - Silva, Elidiomar Ribeiro da (1994)
Aspects on the biology and ecology of Callibaetis guttatus Navás, 1915 (Insecta: Ephemeroptera: Baetidae) in temporary water bodies of Restinga de Maricá, Rio de Janeiro State, with taxonomical notes. Some aspects on the biology and ecology of C. guttatus were studied since 1986 , in Brejo-canal de Itaipuaçu Marsh and other temporary water bodies of Restinga de Maricá, Maricá, RJ, Brazil. The highest values of density and biomass of the species were obtained in Spring, during the decrease of water level, when the offering of substrate and organic matter for food is usually high The secundary production of C. guttatus was 0.17 g m-2 year-1, with a total production of 22.25 Kg during the period The analysis of the gut contents showed fragments of vegetals in different stages of decomposition, vegetable fibres with intact cells, and many algae. The alimentary Pattern probably varied according to the different limnological phases of the marsh. During the decrease of water level the proportion of filamentous algae increased and vegetable fibres decreased in the diet of C.guttatus. Organic matter in decomposition was high in the gut content. In laboratory, the emergence of subimagines occured after late afternoon. Duration of the subimago (about 10 hours) was relatively short for the Pattern of the genus Callibaetis, and poossibly indicates an adaptation for restricting it at night as a strategy level is decreased to avoid desiccation. ln Summer, when the water low in the marsh, the mayfly population values significantly. On the other hand, a crescent process of dispersal to adjacent water bodies was observed, as small pools and leaf axils of bromeliads. In terms of taxonomy, C. guttatus was related to C. willineri Navás, 1932, C. ferrugineus (Walsh, 1862) and C. pretiosus Banks, 1900 based on characters of venation and color pattern of forewings.